Optimal Degree of Hypothermia in Total Arch Replacement for Type A Aortic Dissection - Wu, Jinlin; Qiu, Juntao; Fang, Zhongrong; Luo, Qipeng; Huang, Yao; Yu, Cuntao; Wang, Guyan (Frontiers in Cardiovascular Medicine, 2021)
Background: We sought to investigate the best degree of hypothermic cardiac arrest (HCA) in type A aortic dissection (TAAD) with a cohort of 1,018 cases receiving total arch replacement from 2013 to 2018 in Fuwai Hospital. Method: The cohort was divided by DHCA (≤24°C, n = 580) vs. MHCA (>24°C, n = 438), and interquartile range (Q1–Q4). Primary endpoints included mortality, stroke, paraplegia, and continuous renal replacement therapy (CRRT), which were summarized as composite major outcomes (CMO). Results: The Odds Ratio (OR) of CMO for MHCA was 0.7 (95% CI: 0.5–1.0, p = 0.06) (unadjusted) and 0.6 (95% CI: 0.4–1.0, p = 0.055) (adjusted). DHCA group tended to have a significantly longer CPB time (175.6 ± 45.6 vs. 166.8 ± 49.8 min, p = 0.003), longer hospital stay (16.0 ± 13.6 vs. 13.5 ± 6.8 days, p < 0.001), and ICU stay [5.0 (3.9–6.6) vs. 3.8 (2.0–5.6) days]. A significantly greater blood loss was observed in DHCA group, with a greater requirement for RBC and platelet transfusion. Of note, MHCA showed a significant protective effect (60% risk reduction) for older patients (above 60 years) (OR 0.4; 95% CI: 0.2–0.8; p = 0.009). By quartering, Q1 had significantly higher mortality (10.9%) than Q4 (5.2%) (p = 0.035). For other comparisons, the gap was significantly widened in quartering between Q1 and Q4, i.e., the lower the temperature, the worse the outcomes, and vice versa. Propensity score matching and sensitivity analyses confirmed the above findings. Conclusions: A paradigm change from DHCA to MHCA may be encouraged in TAAD arch operation, especially for the elderly.